2022
DOI: 10.1111/jipb.13331
|View full text |Cite
|
Sign up to set email alerts
|

Blue light‐induced phosphorylation of Arabidopsis cryptochrome 1 is essential for its photosensitivity

Abstract: Plants possess two cryptochrome photoreceptors, cryptochrome 1 (CRY1) and cryptochrome 2 (CRY2), that mediate overlapping and distinct physiological responses. Both CRY1 and CRY2 undergo blue light‐induced phosphorylation, but the molecular details of CRY1 phosphorylation remain unclear. Here we identify 19 in vivo phosphorylation sites in CRY1 using mass spectrometry and systematically analyze the physiological and photobiochemical activities of CRY1 variants with phosphosite substitutions. We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…GhSMXL6/7–1/7–2 and GaSMXL6/7–1/7–2 proteins contain two Clp-N motifs and a P-loop structure of hydrolases (Table S 6 ). Functional predictions indicated that the proteins interacting with GhSMXL6/7–1/7–2 and GaSMXL6/7–1/7–2 are mainly involved in bud development and branching, including WUSCHEL (WUS) [ 37 ], BELL1 (BEL1) [ 38 ], and myb domain protein 5 (MYB5) [ 39 ]; transcription factors involved in the regulation of plant growth and development, such as basic leucine zipper (bZIP) [ 40 ], GRAS [ 41 ], and AP2/ERF [ 42 ]; proteins related to phytohormone signaling pathways such as gibberellin 2-beta-dioxygenase 2 (GA2OX2) [ 43 ] and GA-stimulated transcript 1 (GAST1) [ 44 ], involved in the gibberellin pathway; proteins that respond to red/far-red light and anthocyanin formation, such as cryptochrome circadian regulator 1 (CRY1) [ 45 ] and cytochrome P450 (P450) [ 46 ]; proteins involved in metabolic biosynthesis pathways, such as trehalose-6-phosphate synthase (TPS) [ 47 ], hexokinase 2 (HXK2) [ 48 ], and dehydration-responsive element-binding (DREB) [ 49 ]. These results suggest that the target proteins of GhSMXL6/7–1/7–2 are highly expressed in buds and floral organs and participate in biological processes related to branching development, phytohormone signaling, light response, and metabolic biosynthesis pathways, which provides a basis for further investigations into the functional mechanism of SMXL6/7–1/7–2 genes.…”
Section: Resultsmentioning
confidence: 99%
“…GhSMXL6/7–1/7–2 and GaSMXL6/7–1/7–2 proteins contain two Clp-N motifs and a P-loop structure of hydrolases (Table S 6 ). Functional predictions indicated that the proteins interacting with GhSMXL6/7–1/7–2 and GaSMXL6/7–1/7–2 are mainly involved in bud development and branching, including WUSCHEL (WUS) [ 37 ], BELL1 (BEL1) [ 38 ], and myb domain protein 5 (MYB5) [ 39 ]; transcription factors involved in the regulation of plant growth and development, such as basic leucine zipper (bZIP) [ 40 ], GRAS [ 41 ], and AP2/ERF [ 42 ]; proteins related to phytohormone signaling pathways such as gibberellin 2-beta-dioxygenase 2 (GA2OX2) [ 43 ] and GA-stimulated transcript 1 (GAST1) [ 44 ], involved in the gibberellin pathway; proteins that respond to red/far-red light and anthocyanin formation, such as cryptochrome circadian regulator 1 (CRY1) [ 45 ] and cytochrome P450 (P450) [ 46 ]; proteins involved in metabolic biosynthesis pathways, such as trehalose-6-phosphate synthase (TPS) [ 47 ], hexokinase 2 (HXK2) [ 48 ], and dehydration-responsive element-binding (DREB) [ 49 ]. These results suggest that the target proteins of GhSMXL6/7–1/7–2 are highly expressed in buds and floral organs and participate in biological processes related to branching development, phytohormone signaling, light response, and metabolic biosynthesis pathways, which provides a basis for further investigations into the functional mechanism of SMXL6/7–1/7–2 genes.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the oligomerized CRYs transduce the light signal by modulating the CRY complexes with or without changing the affinity between CRYs and CRY-interacting proteins (see below). Third, photoexcited CRYs are inactivated by interacting with BICs (Blue-light Inhibitor of Cryptochromes) that directly inhibit CRY oligomerization ( Wang et al 2016 ; Ma et al 2020a , 2020b ) and with 4 protein kinases PPKs (PPK1-4) that phosphorylate CRYs at more than 20 serine and threonine residues to not only stimulate CRY activity but also promote CRY ubiquitination and degradation ( Shalitin et al 2002 ; Liu et al 2017 ; Gao et al 2022 ). Two distinct E3 ubiquitin ligases, Cul4 COP1/SPAs and Cul3 LRBs , catalyze CRY polyubiquitination to promote CRY degradation by the 26S proteosome ( Shalitin et al 2002 ; Chen et al 2021 ; Liu et al 2022 ; Miao et al 2022 ).…”
Section: Cryptochromesmentioning
confidence: 99%
“…CRYs interact with the E3 ubiquitin ligase COP1 protein, forming a complex that regulates light−dependent protein degradation [ 54 , 55 ]. COP1 suppresses photomorphogenic development in the dark by targeting transcription factors, including the bZIP protein HY5, for degradation.…”
Section: The Light Signaling Pathwaymentioning
confidence: 99%